Common variants in MAEA gene contributed the susceptibility to osteoporosis in Han Chinese postmenopausal women - Xuan Cai; Jun Dong; Teng Lu; Liqiang Zhi; Xijing He (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Osteoporosis (OP) is a complex bone metabolism disorder characterized by the loss of bone minerals and an increased risk of bone fracture. A recent study reported the relationship of the macrophage erythroblast attacher gene (MAEA) with low bone mineral density in postmenopausal Japanese women. Our study aimed to investigate the association of MAEA with postmenopausal osteoporosis (PMOP) in Han Chinese individuals. Methods A total of 968 unrelated postmenopausal Chinese women comprising 484 patients with PMOP and 484 controls were recruited. Four tag single nucleotide polymorphisms (SNPs) that covered the gene region of MAEA were chosen for genotyping. Single SNP and haplotypic association analyses were performed, and analysis of variance was conducted to test the correlation between blood MAEA protein level and genotypes of associated SNPs. Results SNP rs6815464 was significantly associated with the risk of PMOP. The C allele of rs6815464 was strongly correlated with the decreased risk of PMOP in our study subjects (OR[95% CI]=0.75[0.63-0.89], P=0.0015). Significant differences in MAEA protein blood levels among genotypes of SNP rs6815464 were identified in both the PMOP (F=6.82, P=0.0012) and control groups (F=11.5, P=0.00001). The C allele was positively associated with decreased MAEA protein levels in blood. Conclusion This case-control study on Chinese postmenopausal women suggested an association between SNP rs6815464 of MAEA and PMOP. Further analyses showed that genotypes of SNP rs6815464 were also associated with the blood level of MAEA protein.